Exchange rate misalignment and external imbalances: What is the optimal monetary policy response? - Giancarlo Corsetti; Luca Dedola; Sylvain Leduc (European Central Bank (ECB), 2023)
How should monetary policy respond to excessive capital inflows that appreciate the currency and widen the external deficit? Using the workhorse two-country open-macro model, we derive a quadratic approximation of the utility-based global loss function in incomplete market economies, and solve for the optimal targeting rules under cooperation. The optimal monetary stance is expansionary if the exchange rate pass-through (ERPT) on import prices is complete, contractionary if nominal rigidities attenuate ERPT. Excessive capital inflows, however, may lead to currency undervaluation instead of overvaluation for some parameter values. The optimal stance is then invariably expansionary to support domestic demand.
Keywords: E44; E52; E61; F41; F42; 330; Currency misalignment; trade imbalances; asset markets and risk sharing; optimal targeting rules; international policy cooperation; exchange rate pass-through